2022
DOI: 10.1097/tp.0000000000004312
|View full text |Cite
|
Sign up to set email alerts
|

Isavuconazole for the Treatment of Invasive Mold Disease in Solid Organ Transplant Recipients: A Multicenter Study on Efficacy and Safety in Real-life Clinical Practice

Abstract: Background. Isavuconazole has theoretical advantages over other mold-active triazoles for the treatment of invasive aspergillosis and mucormycosis after solid organ transplantation (SOT). The available clinical experience, nevertheless, is scarce. Methods. We performed a retrospective study including all adult SOT recipients with proven or probable invasive mold disease (IMD) that received isavuconazole for ≥24 h as first-line or salvage therapy at 10 Spanish centers between September 2017 and November 2021. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
1
5
0
1
Order By: Relevance
“…In our study, these IFIs accounted for most cases (87%) where ISA was used as targeted therapy. The success rate for proven/probable IFI was 54%, which is superior to rates reported in prospective trials [ 8 , 9 ] but similar to those of other real-life observational studies [ 14 , 17 ]. In addition, ISA was used as empiric therapy for possible IFI.…”
Section: Discussionsupporting
confidence: 77%
“…In our study, these IFIs accounted for most cases (87%) where ISA was used as targeted therapy. The success rate for proven/probable IFI was 54%, which is superior to rates reported in prospective trials [ 8 , 9 ] but similar to those of other real-life observational studies [ 14 , 17 ]. In addition, ISA was used as empiric therapy for possible IFI.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, if there is a suspected breakthrough IFI while receiving echinocandin prophylactic therapy L-AMB would allow for a broad-spectrum antifungal treatment, while maintaining the antineoplastic therapy due to the lack of drug–drug interactions [ 10 ]. Isavuconazole, which appears to be a lesser CYP3A4 inhibitor has a good safety profile and a more easily managed drug–drug interaction with immunosuppressive agents, could also be a possible treatment alternative [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports showed that ISA had become a new option for the treatment of IFD, with an overall response rate of 35–87% [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In our study, we had an overall response rate of 75%.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the efficacy and safety of ISA have mainly been reported in clinical trials, rarely in real-world studies. Most of these studies have shown that ISA is not inferior to VOR and AmB with respect to the treatment of IFD, presenting a 35–87% clinical response and a 6–38% 42-day mortality [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Given that it was only approved in China at the end of 2021 for the treatment of IA and IM in adults, there is a lack of real-world evidence concerning the Chinese population.…”
Section: Introductionmentioning
confidence: 99%